A DIVE INTO LANDSCAPE OF INDIAN ENVIRONMENTAL LAWS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
COP 28 led to increased recognition and momentum for addressing the climate and biodiversity crises. Governments were urged to include ecosystems, biodiversity, and carbon stores in their national climate action plans Nature-based solutions were also acknowledged as key to mitigating climate change impacts. India being one of participant country is also expected to fulfil these goals. India has enacted numerous environmental laws to address these issues; however, it is essential to examine the current investigative mechanisms under various Indian environmental statutes to understand their effectiveness. The paper compares Indian environment agency with other agencies of world emphasizing on the procedures of investigation and inquiry under the various environmental laws of India. Effective investigation and inquiry mechanisms are necessary for environmental law enforcement to bring about compliance, address violations, and promote sustainable development. Undoubtedly, each of the above-listed ecological laws has been given measures and shaped by the objects set out by the law; nonetheless, all head towards a mutual goal, i.e., the protection of the environment. Enhancing these mechanisms through increased coordination, more technology infusion, and further robust legal frameworks will empower environmental governance in India even more.